“Sandpaper. Yeah.”: Educators’ embodied insights into comprehensive sexual health education pedagogy - Hare, Kathleen (Kaye) A. (Canadian Journal of Education / Revue canadienne de l'éducation, 2024)
In this arts-informed inquiry, I examine Canadian sex educators’ embodied sense-making of comprehensive sexual health education (CSHE). I seek to understand how educators use their bodies to negotiate contested pedagogical terrain in order to gain insights into conflicting patterns observed in the literature, as well as to challenge how educators’ personal pedagogies may be implicated in uneven enactments of CSHE. Using sensory ethnographic principles, I focus inquiry on educators’ embodied experiences of contentious pedagogical practices, including the over-reliance on institutionalized forms of knowledge. I conceptualize their experiences as “interchange”— the sense of simultaneous bodily gaining and giving in response to the social-political demands of teaching CSHE. I analyze two focal experiences of interchange—namely, Feeling Right(s) and Be/ing Schooled—to highlight paradoxical frictions of educators’ personal and pedagogical anti-oppressive aims. Last, I utilize Maclaren’s concept of “unfreedom” to discuss addressing problematic CSHE practices as an intersubjective project.